Assessing the best criteria and the implications of neglecting communication skills and knowledge among estate agents in Shah Alam - Che Teh, Muhammad Mustaqim (2024)
This research project is focus to assessing the best criteria and the implication of neglecting communication skills and knowledge among estate agents in Shah Alam. The study aims to identify the best criteria for an estate agent and to determine the implication of neglecting communication skills and knowledge for an estate agent. Through qualitative methods, including using the primary data such as interviews with Shah Alam’s estate agents and a thorough literature review, the research explores the best criteria and the implication of neglecting communication skills and knowledge that required for estate agent to excel in their roles. By analysing data using NVivo 14 software, the study uncovers patterns and themes related to best criteria and the implication of neglecting communication skills and knowledge among estate agents. The findings highlight the codes from the first study, which was effective in identifying 39 item codes from the four-interview conducted. The data collected from interview have been divided into several themes then were separated into various codes. The themes in this research were the best criteria and the implication of neglecting communication skill and knowledge. All the data collected were analysis based on the research objective one and research objective two. From the analysis made, the researcher concluded the interviewees’ responds and choose the agreed best criteria and the implication of neglecting communication skills and knowledge among the interviewees based on their perspective into the next chapter. This research contributes valuable insights by addressing the best criteria and the implication of neglecting communication skills and knowledge among estate agent in giving their best services to clients in the future. Thus, the researcher also stated the recommendations for the future studies to be referred in the last chapter of this research.